2-Cl-MGV-1 Ameliorates Apoptosis in the Thalamus and Hippocampus and Cognitive Deficits After Cortical Infarct in Rats. Issue 12 (December 2017) - Chen, Yicong; Veenman, Leo; Singh, Sukhdev; Ouyang, Fubing; Liang, Jiahui; Huang, Weixian; Marek, Ilan; Zeng, Jinsheng; Gavish, Moshe
Abstract : Background and Purpose—: Focal cortical infarction causes neuronal apoptosis in the ipsilateral nonischemic thalamus and hippocampus, which is potentially associated with poststroke cognitive deficits. TSPO (translocator protein) is critical in regulating mitochondrial apoptosis pathways. We examined the effects of the novel TSPO ligand 2-(2-chlorophenyl) quinazolin-4-yl dimethylcarbamate (2-Cl-MGV-1) on poststroke cognitive deficits, neuronal mitochondrial apoptosis, and secondary damage in the ipsilateral thalamus and hippocampus after cortical infarction. Methods—: One hundred fourteen hypertensive rats underwent successful distal middle cerebral artery occlusion (n=76) or sham procedures (n=38). 2-Cl-MGV-1 or dimethyl sulfoxide as vehicle was administrated 2 hours after distal middle cerebral artery occlusion and then for 6 or 13 days (n=19 per group). Spatial learning and memory were tested using the Morris water maze. Secondary degeneration and mitochondrial apoptosis in the thalamus and hippocampus were assessed using Nissl staining, immunohistochemistry, terminal deoxynucleotidyl transferase dUTP nick end labeling, JC-1 staining, and immunoblotting 7 and 14 days after surgery. Results—: Infarct volumes did not significantly differ between the vehicle and 2-Cl-MGV-1 groups. There were more neurons and fewer glia in the ipsilateral thalamus and hippocampus in the vehicle groups than in the sham-operated group 7 and 14 days post–distal middle cerebral artery occlusion. 2-Cl-MGV-1 significantly ameliorated spatial cognitive impairment and decreased neuronal death and glial activation when compared with vehicle treatment ( P <0.05). The collapse of mitochondrial transmembrane potential and cytoplasmic release of apoptosis-inducing factors and cytochrome c was prevented within the thalamus. Caspase cleavage and the numbers of terminal deoxynucleotidyl transferase dUTP nick end labeling + or Nissl atrophic cells were reduced within the thalamus and hippocampus. This was accompanied by upregulation of B-cell lymphoma 2 and downregulation of Bax ( P <0.05). Conclusions—: 2-Cl-MGV-1 reduces neuronal apoptosis via mitochondrial-dependent pathways and attenuates secondary damage in the nonischemic thalamus and hippocampus, potentially contributing to ameliorated cognitive deficits after cortical infarction. Abstract : Supplemental Digital Content is available in the text.